2011
DOI: 10.1177/0269215511410730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early compensation of distal motor deficiency by the Chignon ankle-foot orthosis on gait in hemiplegic patients: a randomized pilot study

Abstract: Early compensation of distal motor deficiency by the Chignon ankle-foot orthosis improves the immediate gait of hemiplegics more than the standard ankle-foot orthosis and seems to modify motor recovery processes in the legs after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 31 publications
1
38
0
1
Order By: Relevance
“…659 A recent meta-analysis and systematic review suggested the potential mechanism(s) associated with the above effects by demonstrating a positive effect of an AFO on ankle kinematics, knee kinematics in stance phase, kinetics, and energy cost. 658 Two RCTs 763,764 showed that after 3 months of AFO use, AFO users had better mobility while wearing the AFO. One small RCT 764 found that although a dynamic hinged AFO improved ambulatory function over a standard AFO, it induced some dependence; the standard AFO group performed better after 3 months of use when walking without any orthosis.…”
Section: Level Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…659 A recent meta-analysis and systematic review suggested the potential mechanism(s) associated with the above effects by demonstrating a positive effect of an AFO on ankle kinematics, knee kinematics in stance phase, kinetics, and energy cost. 658 Two RCTs 763,764 showed that after 3 months of AFO use, AFO users had better mobility while wearing the AFO. One small RCT 764 found that although a dynamic hinged AFO improved ambulatory function over a standard AFO, it induced some dependence; the standard AFO group performed better after 3 months of use when walking without any orthosis.…”
Section: Level Of Evidencementioning
confidence: 99%
“…658 Two RCTs 763,764 showed that after 3 months of AFO use, AFO users had better mobility while wearing the AFO. One small RCT 764 found that although a dynamic hinged AFO improved ambulatory function over a standard AFO, it induced some dependence; the standard AFO group performed better after 3 months of use when walking without any orthosis. With respect to the patient's perspective, it is important to determine whether an individual is willing to wear an AFO regularly.…”
Section: Level Of Evidencementioning
confidence: 99%
“…Regarding the duration of use and adaptation to orthoses, a tendency toward an improvement in gait velocity and cadence was found with increased usage in the studies carried out by Erel et al24 ) and De Sèse et al25 ) . However, Thijssen et al18 ) only found an immediate increase in gait velocity with the use of an AFO, there being no changes in either gait velocity or cadence after three weeks of familiarization with the orthosis.…”
Section: Discussionmentioning
confidence: 91%
“…While Iwata et al16 ) , Wang et al17 ) and Hiroaki et al22 ) report improvements in cadence, Chen et al11 ) , Gok et al15 ) , Thijssen et al18 ) and Bleyenheuft et al19 ) found no significant change in this variable. However, the same was true of gait velocity, as the majority of studies report significant improvements in gait velocity with the use of an AFO5, 15,16,17,18,19,20, 22, 24, 25 ) . The exception was the study by Lewallen et al23 ) , but the authors compared gait velocity between use of rigid and articulated orthoses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation